Synthesis, properties, antitumor and antibacterial activity of new Pt(II) and Pd(II) complexes with 2, 2′-dithiobis(benzothiazole) ligand. Issue 8 (15th April 2017) - Rubino, Simona; Busà, Rosalia; Attanzio, Alessandro; Alduina, Rosa; Di Stefano, Vita; Girasolo, Maria Assunta; Orecchio, Santino; Tesoriere, Luisa
Graphical abstract: Mono- and binuclear Pt(II) (1 ) and Pd(II) (2 ) complexes with 2, 2′-dithiobis(benzothiazole) ligand were synthesized, structural characterized and their antimicrobial and antitumor activity were studied. Only1 showed a dose- and time-dependent cytotoxic activity and apoptosis against two tumor cell lines MCF-7 and HepG2 but both1 and2 exhibited antimicrobial activity. Highlights: Pt(II) and Pd(II) complexes were synthesized with DTBTA ligand. Complex1 and2 exhibited antimicrobial activity. Only complex1 showed a dose- and time-dependent cytotoxic activity against two tumor cell lines associated to cell apoptosis. Abstract: Mono- and binuclear Pt(II) and Pd(II) complexes with 2, 2′-dithiobis(benzothiazole) (DTBTA) ligand are reported. [Pt(DTBTA)(DMSO)Cl]Cl∙CHCl3 (1 ) and [Pd2 (µ-Cl)2 (DTBTA)2 ]Cl2 (2 ) have been synthesized and structurally characterized by elemental analysis, IR, 1 H and 13 C NMR spectroscopy, MS spectrometry and the content of platinum and palladium was determined using a flame atomic spectrometer. Two different coordination modes of1 and2 complexes were found; in both complexes, the coordination of Pt(II) and Pd(II) ions involves the N(3) atoms of the ligand but the binuclear complex2, is a cis- chloro-bridged palladium complex. Evaluation of their in vitro antitumor activity against two human tumor cell lines human breast cancer (MCF-7) and hepatocellular carcinoma (HepG2); and their antimicrobial activity against Escherichia coli and Kokuria rhizophila was performed. Only complex1 showed a dose- and time-dependent cytotoxic activity against the two tumor cell lines, associated to apoptosis and accumulation of treated cells in G0/G1 phase of cell cycle, while both1 and2 exhibited antimicrobial activity with complex1 much more potent. The study on intracellular uptake in both MCF-7 and HepG2 cell lines revealed that only platinum of complex1 is present inside the cells, suggesting a different mode of action of the two compounds. This was also in agreement with the results obtained for the antitumor and antibacterial activity.